Spontaneous Common Bile Duct Perforation on The Background of Pancreatic Lithiasis: A Case Report and The Review of The Literatures (Journal of Paediatric Surgeons of Bangladesh, 2014)
Spontaneous bile duct perforation (SBDP) is a relatively rare condition. The cause of SBDP is still speculative. Presentation , site of the perforation and management varies. Pancreatic lithiasis ( PL) is a very rare entity in childhood. Biliary perforation on the background of PL is still a rare event. This is a case report of 10 years old girl presented as acute abdomen with theclinical diagnosis of acute on chronic pancreatitis, for which conservative treatment followed by laparotomy was carried out.Common bile duct (CBD) perforation was found near its junction with cystic duct. T tube was instituted and a drain was kept in situ. Postoperative period ( POP )was uneventful. T Tube Cholangiogram was carried out on 12th postoperative day( POD ) that showed dye had passed to duodenum easily and patency and caliber of the CBD was found normal. Multiple stones were noted in the vicinity. No apparent cause of CBD perforation was found. After one month, in follow up visit the patient was found alright. She was asked to come after 3 months for further evaluation. The plan is to evaluate the patients conditions clinically and biochemically and to do an MRCP to see details ofpancreatic pathology. As SBDP in children with PL is a rare condition, high index of suspicion is needed for early diagnosis and proper management of such patient.DOI: http://dx.doi.org/10.3329/jpsb.v2i2.19553